Thermosphere-ionosphere response to a severe magnetic storm: A case study - Mansilla, Gustavo Adolfo (2012)
This paper reports the response of the ionosphere-thermosphere system to an intense geomagnetic storm. For that, data taken by instruments on board Dynamic Explorer 2 at heights of the F2-layer (molecular nitrogen N 2 and atomic oxygen O compositions, neutral temperature Tg and electron density Ne) were used. The ionospheric response is characterized by a negative storm effect expanding from mid-high to low latitude. It is observed during this severe geomagnetic storm that negative effects were caused mainly by an increase in molecular nitrogen composition N 2 and almost no changes in atomic oxygen composition O.